School Deworming - World Bank (Washington, DC, 2012)
Worms infect more than one third of the world's population, with the most intense infections in children and the poor. In the poorest countries, children are likely to be infected from the time they stop breast-feeding, and to be continually infected and re-infected for the rest of their lives. Only rarely does infection have acute consequences for children. Instead, the infection is long-term and chronic, and can negatively affect all aspects of a child's development: health, nutrition, cognitive development, learning and educational access and achievement. All the common worm infections in school-age children can be treated effectively with two single dose pills: one for all the common intestinal worms (hookworms, roundworms, and whipworms) and the other for schistosomiasis (bilharzia). The treatment is safe, even when given to uninfected children.